Teaching Values through Animation: Analyzing Family Dynamics in Encanto for Character Education - Bakara, Uly Debora; Neolaka, Grace Amialia Anfetonanda (JUPE : Jurnal Pendidikan Mandala, 2025)
Character education plays a significant role in shaping children’s moral and emotional development. As digital media continues to influence young audiences, animated films have become an effective platform for teaching essential values through storytelling and character representation. This study explores Encanto (2021), a Disney animated film that presents a multigenerational family navigating emotional expectations, communication struggles, and self-discovery. The purpose of this study is to analyze how Encanto can be used as a medium to support character education, particularly by examining family communication and its impact on individual growth and resilience. This qualitative research applies the theory of Mise en Scène by Manon de Reeper to analyze visual elements and Family Systems Theory by Murray Bowen to examine the emotional dynamics and communication patterns within the Madrigal family. Selected scenes from the film are analyzed to identify core values such as empathy, responsibility, emotional honesty, and mutual respect. The findings show that Encanto offers strong educational potential for promoting character values and healthy communication practices, making it a relevant resource for educators, parents, and practitioners in early childhood education.